Death Penalty for Corruptors in Non-Natural Disaster Fund in The Presidential Decree No. 12 of 2020 [Pidana Mati Bagi Koruptor Dana Bencana Non Alam: Studi Terhadap Konsekuensi Keputusan Presiden Nomor 12 Tahun 2020] - Amrullah Bustamam (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2020)
Abstract: The death penalty is the principal punishment in Article 10 of the Criminal Code and is also contained in Article 2 paragraph 2 of Law no. 31 of 1999 concerning the Eradication of Corruption. The pros and cons of the possibility that the Covid-19 pandemic fund corruptors were sentenced to death became a hot issue at the end of 2020, after the appointment of the Minister of Social Affairs as a suspect in the corruption case of social assistance funds. This study is more focused on whether the corruptors of aid funds during the Covid -19 pandemic can be sentenced to death if it is related to the consequences of the issuance of Presidential Decree No. 12 of 2020 which stipulates Covid -19 as a Non-natural disaster. The results of this study are a logical consequence of the determination of the Covid-19 outbreak as a non-natural disaster according to Presidential Decree No. 12/2020, the death penalty can't be imposed on corrupt perpetrators considering that in the explanation of Article 2 paragraph 2 of Law no. 31 of 1999 requires natural disasters as a condition for the phrase certain circumstances so that corruptors can be sentenced to death. Abstrak: Pidana Mati merupakan hukuman Pokok dalam Pasal 10 KUHP, dan juga termuat dalam Pasal 2 ayat 2 UU Nomor 31 Tahun 1999 tentang Pemberatasan Korupsi. Pro dan Kontra kemungkinan para koruptor dana Pandemi Covid -19 di pidana Mati menjadi isu yang hangat di akhir tahun 2020, pasca penetapan Menteri Sosial sebagai tersangka kasus korupsi dana bantuan sosial. Studi ini lebih mengarah pada apakah koruptor dana bantuan masa pandemi Covid -19 ini dapat di hukum mati jika di hubungkan dengan konsekuensi dari dikeluarkannya Kepres No. 12 Tahun 2020 yang menetapkan Covid -19 sebagai bencana Non-alam. Hasil studi ini adalah Konsekuensi logis dari penetapan wabah Covid-19 ini sebagai bencana non –alam sesuai Kepres No. 12/2020 adalah sangatlah mustahil pidana mati dapat dijatuhkan kepada pelaku Koruptor mengingat bahwa dalam penjelasan Pasal 2 ayat 2 UU No. 31 Tahun 1999 mengharuskannya bencana alam sebagai syarat frasa “keadaan tertentu” agar dapat di jatuhi pidana mati bagi koruptor.